(untitled) - Kardong, Kenneth V. (Boston, MA., 2005)
This book offers an introduction to the principles and significance of Darwinian evolution. It differs from most other textbooks on evolution in three fundamental ways: First, it is intended for students taking evolution early in their studies. Second, it examines the intellectual significance of Darwinian evolution. Third, the text departs from the standard treatment of evolution in other textbooks, wherein the arguments are reductionist, molecular, and overwhelmingly genetic in emphasis.
Keywords: Evolution ( Biology ); Textbooks